Progress of autonomic disturbances in narcolepsy type 1 - Wang, Ying; Sun, Qingqing; Tang, Qi; Zhang, Yanan; Tang, Mingyang; Wang, Dong; Wang, Zan (Frontiers in Neurology, 2023)
Narcolepsy type 1 is a chronic sleep disorder, which is characterized by a specific loss of hypocretin neurons in the lateral hypothalamus and a reduced level of hypocretin-1 in cerebrospinal fluid. Hypocretin deficiency is closely related to autonomic dysfunction. Patients with narcolepsy type 1 often have various autonomic symptoms, such as cardiovascular, nervous, digestive, urinary, reproductive, pupillary, and body temperature regulation. This article summarized the autonomic dysfunction and possible mechanisms in narcolepsy type 1, and thus strengthen recognition and intervention of clinical disturbances.